2022
DOI: 10.1002/joc.7559
|View full text |Cite
|
Sign up to set email alerts
|

Global water availability and its distribution under the Coupled Model Intercomparison Project Phase Six scenarios

Abstract: Changes in the hydrological cycle have widespread consequences and remain uncertain under climate change. We analyse the changes in major water components of the hydrological cycle, that is, precipitation (P), runoff (Q), evapotranspiration (E), precipitation minus evapotranspiration (P − E), and terrestrial water storage (S), and quantify the uncertainties across the 21st century with Phase Six of the Coupled Model Intercomparison Project (CMIP6) simulations. The multimodel ensemble based on over 10 GCMs show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…This dataset has been applied to global hydrology, climate and other field studies (e.g., R.-J. Wu, Lo, and Scanlon 2021;Lehmann, Vishwakarma, and Bamber 2022;X. Li and Li 2022).…”
Section: Precipitation Runoff and Grace Datamentioning
confidence: 99%
“…This dataset has been applied to global hydrology, climate and other field studies (e.g., R.-J. Wu, Lo, and Scanlon 2021;Lehmann, Vishwakarma, and Bamber 2022;X. Li and Li 2022).…”
Section: Precipitation Runoff and Grace Datamentioning
confidence: 99%
“…In this context, we build upon prior studies that have already shed light on certain identified issues within these model frameworks. For instance, MERRA-2 has shown a robust land-atmosphere coupling [41], ERA5 has exhibited P overestimation in specific regions [42], and certain biases have been identified in CMIP6 soil moisture and precipitation variables, particularly in high latitude regions [43,44]. While these recognized issues have been observed at regional scales, their global consistency remains uncertain.…”
Section: Reanalysis Modelsmentioning
confidence: 99%
“…Secondly, most of the previous studies assessed bias correction methods using global climate outputs from CMIP5 or its previous generations (Switanek et al, 2017). CMIP6 models have a higher climate sensitivity than previous generations, where hotter temperature projections are expected (Forster et al, 2020;Gettelman et al, 2019;Li and Li, 2022).…”
Section: Introductionmentioning
confidence: 99%